Prevalence of gastrointestinal helminths in domestic bison herds in northwestern Alberta. - Dies, K H (2001)
A fecal survey was conducted to determine the prevalence of gastrointestinal helminth eggs found in 431 domestic bison from 22 herds. Eggs detected (percent of herds affected in parentheses) were: strongyle-type (100%), Capillaria sp. (63.6%), Moniezia sp. (54.6%), Nematodirus sp. (50%), Trichuris sp. (40.9%), and Strongyloides sp. (9.1%).